Making a significant place: excavations at the Late Mesolithic site of Langley's Lane, Midsomer Norton, Bath and North-East Somerset. Issue 1 (2nd January 2019) - Lewis, Jodie; Rosen, Caroline; Booth, Rona; Davies, Paul; Allen, Martyn; Law, Matt
ABSTRACT: Excavations at the site of Langley's Lane, Bath and North-East Somerset, have revealed an important sequence of Late Mesolithic activity focused around an active tufa spring. The sequence of activity starts off as an aurochs kill and primary butchery site. Culturally appropriate depositional practices occur through the placement of a selection of bone in the wetland of the spring and the digging of pits around the spring margins. The spring at Langley's Lane continued to be visited and more animal bone and lithic material was placed in the wetland. Finally, visits to the site involved yet more formalized activity in the form of pit digging and the creation of a stone surface. Activities such as these are difficult to locate in the archaeological record and Mesolithic ritual activity rare, making this a site of some significance to studies of Mesolithic NW Europe.